2009
DOI: 10.1094/phyto-99-7-0792
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing the Nomenclature for Clonal Lineages of the Sudden Oak Death Pathogen, Phytophthora ramorum

Abstract: Phytophthora ramorum, the causal agent of sudden oak death and ramorum blight, is known to exist as three distinct clonal lineages which can only be distinguished by performing molecular marker-based analyses. However, in the recent literature there exists no consensus on naming of these lineages. Here we propose a system for naming clonal lineages of P. ramorum based on a consensus established by the P. ramorum research community. Clonal lineages are named with a two letter identifier for the continent on whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…• The distribution of lineages was reported as follows (using the nomenclature suggested by Grünwald et al, 2009): NA1 in North American nurseries and forests, NA2 in North American nurseries, EU1 in European nurseries. The evidence presented in that study indicated that introduction in nature in the USA most likely had been unwittingly aided by the sale and/or movement of infected nursery plants.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…• The distribution of lineages was reported as follows (using the nomenclature suggested by Grünwald et al, 2009): NA1 in North American nurseries and forests, NA2 in North American nurseries, EU1 in European nurseries. The evidence presented in that study indicated that introduction in nature in the USA most likely had been unwittingly aided by the sale and/or movement of infected nursery plants.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…As the understory vegetation sustains the pathogen and allows efficient proliferation (sporulation) in an epidemic of SOD, the appearance of "sudden larch death" represents a new life strategy of P. ramorum, because it is shown to sporulate efficiently high in the tree canopy. Isolates of P. ramorum examined to date comprise three distinct lineages: EU1, NA1 and NA2 (Ivors et al 2004, Ivors et al 2006, Grünwald et al 2009). The European populations of P. ramorum consist solely of EU1 genotypes and represent predominantly A1 mating type (Grünwald et al 2009, Werres & De Merlier 2003.…”
Section: New Species Of Phytophthora In Nurseries and Natural Ecosystemsmentioning
confidence: 99%
“…Isolates of P. ramorum examined to date comprise three distinct lineages: EU1, NA1 and NA2 (Ivors et al 2004, Ivors et al 2006, Grünwald et al 2009). The European populations of P. ramorum consist solely of EU1 genotypes and represent predominantly A1 mating type (Grünwald et al 2009, Werres & De Merlier 2003. NA1 consists of only a single genotype, which is responsible for SOD and is the most widespread genotype in US nurseries (Ivors et al 2006).…”
Section: New Species Of Phytophthora In Nurseries and Natural Ecosystemsmentioning
confidence: 99%
“…Growth rate was determined on V8 agar by measuring the colony diameter after 7 days' incubation at 20°C in the dark. Sporangia were dislodged from 10-day-old cultures on diluted (10% clarified juice) V8 agar using 20 ml of sterile MilliQ water and a glass rod, then quantified a Lineage according to Grünwald et al (2009). Multilocus genotype according to Vercauteren et al (2010) b Different from EU1MG1 with an AFLP marker c R resistant; S sensitive.…”
Section: Phenotypic Characterization In Vitromentioning
confidence: 99%